1984
DOI: 10.1111/j.1432-1033.1984.tb07916.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of H10‐ and H5‐like protein structure and distribution in higher and lower eukaryotes

Abstract: A survey of H1" and H5-like proteins has been conducted through a range of higher and lower eukaryotic species. All mammals examined possessed H 1" proteins, although in variable amounts, and the protein's structure was well conserved, though not invariant. The testis-specific histone Hlt (from rat) did not have an HIo-like structure and it appears that HI" does not occur in spermatocytes in any form. The results also show that Xenopus laevis contains HIo-like proteins, but lower, non-vertebrate eukaryotes (a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
2

Year Published

1988
1988
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 42 publications
1
22
0
2
Order By: Relevance
“…Elsewhere we presented evidence that a yeast analogue of histone H 1 could be detected immunologically as a contaminant in some HMG preparations (12). Positive immunochemical identification of H1-like proteins in yeast has also been reported by others (6,8). As a continuation of this work (12), we attempted the identification in the yeast genome of nucleotide sequences homologous to the H 1 gene from sea urchin.…”
supporting
confidence: 61%
“…Elsewhere we presented evidence that a yeast analogue of histone H 1 could be detected immunologically as a contaminant in some HMG preparations (12). Positive immunochemical identification of H1-like proteins in yeast has also been reported by others (6,8). As a continuation of this work (12), we attempted the identification in the yeast genome of nucleotide sequences homologous to the H 1 gene from sea urchin.…”
supporting
confidence: 61%
“…In the few nuclei still isolatable at 12 hr after H1 induction, chromatin was more highly condensed than in normal yeast nuclei. This hypercondensation may be achieved by the concerted action ofthe exogenous H1 and of an endogenous Hl-like protein (5)(6)(7). Yeast DNA appears rather compacted even in the interphase nucleus, with a compaction factor (the ratio of the length of total genomic DNA to the diameter of the nucleus) of roughly 2000 (26).…”
mentioning
confidence: 99%
“…4. Previous reports indicated that the N terminus of the H1 0 proteins is blocked, restricting the determination of primary structure in that region (15,31). However, as shown in Table I, we did sequence all RP-HPLC fractions including the N-terminal fraction I of Fig.…”
Section: Fig 2 Au-page Of the Four Histone H1mentioning
confidence: 98%